2022
DOI: 10.3390/molecules27144404
|View full text |Cite
|
Sign up to set email alerts
|

MoO3 Nanobelt-Modified HMCM-49 Zeolite with Enhanced Dispersion of Mo Species and Catalytic Performance for Methane Dehydro-Aromatization

Abstract: The methane dehydro-aromatization reaction (MDA) is a promising methane valorization process due to the conversion of methane to value-added aromatics (benzene, toluene and naphthalene). However, one of the major disadvantages of utilizing zeolite in MDA is that the catalyst is rapidly inactivated due to coke formation, which eventually causes the activity and aromatic selectivity to decrease. Consequently, the process is not conducive to large-scale industrial applications. The reasonable control of Mo site d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 55 publications
(73 reference statements)
0
3
0
Order By: Relevance
“…The first step of metal loading is to select a suitable metal precursor that could improve the dispersion of metal. 132 Yuebing Xu et al found that FeSO 4 is relatively stable under calcination conditions. When FeSO 4 was used as the precursor, it helped to maintain the stable lattice structure of Fe, and the newly generated Fe-oxo active sites were mostly dispersed in the oligonucleus.…”
Section: Improvement Of Metal Dispersibilitymentioning
confidence: 99%
See 1 more Smart Citation
“…The first step of metal loading is to select a suitable metal precursor that could improve the dispersion of metal. 132 Yuebing Xu et al found that FeSO 4 is relatively stable under calcination conditions. When FeSO 4 was used as the precursor, it helped to maintain the stable lattice structure of Fe, and the newly generated Fe-oxo active sites were mostly dispersed in the oligonucleus.…”
Section: Improvement Of Metal Dispersibilitymentioning
confidence: 99%
“…The first step of metal loading is to select a suitable metal precursor that could improve the dispersion of metal . Yuebing Xu et al found that FeSO 4 is relatively stable under calcination conditions.…”
Section: Strategies To Inhibit Carbon Depositionmentioning
confidence: 99%
“…In fact, pure MoO 3 exhibits low activity in selective propane oxidation. The dispersion of MoO x species can be greatly enhanced by loading MoO 3 onto a suitable support material such as SiO 2 . , It has been reported that the high dispersion and isolated active sites on catalysts with low loadings promote the formation of target products such as propylene and acrolein and lead to high catalytic activity for the selective oxidation of propane . By contrast, when the content of active components is increased to a high level, highly aggregated and even crystalline species are formed on the catalyst, which can easily lead to deep oxidation of the reactants. , Fukudome and Suzuki investigated the activity and selectivity of supported VO x in the oxidative dehydrogenation of propane.…”
Section: Introductionmentioning
confidence: 99%